Characterization and performance evaluation of fully biocompatible gelatin-based humidity sensor for health and environmental monitoring - Khan, Maryam; Rehman, Muhammad Muqeet; Khan, Shenawar Ali; Saqib, Muhammad; Kim, Woo Young (Frontiers in Materials, 2023)
Biomaterials will have far reaching effects on solving the ever-rising environmental problems caused by the presently used toxic materials. Disposal of hazardous materials based electronic devices is causing a huge environmental problem in the form of electronic wastes (E-wastes). This study is an effort to contribute in the reduction of E-wastes by presenting the design, fabrication, and performance evaluation of a fully biocompatible humidity sensor with gelatin as the active layer. Gelatin is an excellent choice for humidity sensing because it is a hygroscopic material with the natural ability to attract and absorb water molecules, allowing for an effective detection and measurement of humidity levels in its surrounding environment. We patterned highly conductive (2.05 μΩ-cm) gold (Au) interdigitated electrode (IDE) (50 nm thickness) structure on a glass substrate by using thermal vacuum evaporation followed by the deposition of gelatin thin film by using cost effective technique of spin coating (at 1,500 rpm for 15 s). The device size was 25 mm × 22 mm with a line spacing of 1.50 mm between IDEs. Electrical characterisation was carried out to determine necessary performance parameters of the fully biocompatible humidity sensor and the obtained results exhibited a fast response/recovery time (4/6.30 s), wide operating range (15 %RH to 86 %RH), highly repeatable behaviour of 3 different samples and long lifetime (1 month). Wide variation in the resistance of sensor was observed at extreme humidity sensors ranging from 2.45 MΩ (15 %RH) to 0.12 MΩ (86 %RH). The fabricated sensor was used for the practical applications of health monitoring, touch less sensing, and environment monitoring. Moisture content of multiple commercially available moisturizers was determined by using gelatin based fully biocompatible humidity sensor and the obtained results showed that moisturizing cream had highest moisture content of 87 %RH (0.1 MΩ), followed by 80 %RH (0.30 MΩ) of rose water, and 72 %RH (0.67 MΩ) of baby oil.